Analysis of Marketing Strategies in Increasing the Competitiveness of MSMEs Assisted by PT. Pertamina Hulu Rokan: Case Study in Bintan - Muhammad Arif; Nazrantika Sunarto; Tri Handayani (Newinera Publisher, 2024)
This research investigates the marketing communication approach of Dpoer Bintan MSME which is one of the small and medium scale enterprises promoted by PT. Pertamina Hulu Rokan, and assesses the degree to which these programmes have contributed to improving the competitiveness of the MSME. The role of the mixed-method design means the use of qualitative data collected from the interviews, observations, and documents together with the quantitative data from the customer satisfaction, sales, and the web analytics. The research shows that quality is the defining characteristic underpinned by quality assurance and constant product development that underlay the MSME’s competitive approach in the marketplace and very strong customer satisfaction & brand association. The study also also highlights the significance of digital marketing and the two activities including social media interaction and conversation rate optismisation-in the broadening of the market base and boosting of sales volume. Besides, the increasing strategic partnerships with PT. Pertamina Hulu Rokan and local suppliers have been established to play important roles of enhancing operational efficiency as well as market access thus the research recognize the impacts of relying on supply chain. SWOT analysis offers a broad vision of the MSME scenario in the market and list of strengths and weaknesses such as quality product that the firm offers or lack of capital for marketing, and opportunity and threat like digital marketing that the firm taken or has to face respectively.